Nanoporous PdCr alloys as highly active electrocatalysts for oxygen reduction reaction. Issue 5 (19th January 2016) - Duan, Huimei; Xu, Caixia
Abstract : The NP–Pd75 Cr25 alloy exhibits superior ORR activities with enhanced specific and mass activities as well as higher structural stability. Abstract : A simple and convenient dealloying method is used to prepare nanoporous (NP) PdCr alloys with uniform ligament dimensions and controllable bimetallic ratio. The structural characterization methods demonstrate that the NP–PdCr alloy is comprised of a nanoscaled interconnected network skeleton and hollow channels extending in all three dimensions. Electrocatalytic measurements indicated that the as-made NP–Pd75 Cr25 alloy exhibits superior specific and mass activities as well as higher catalytic stability toward oxygen reduction reaction compared with NP–Pd67 Cr33, NP–Pd, and commercial Pt/C catalysts. X-ray photoelectron spectroscopy and density functional theory calculations both demonstrate that the weakened Pd–O bond and improved ORR performances depend on the downshifted d-band center of Pd due to the alloying of Pd with Cr (25 at%). It is expected that the as-made NP–PdCr alloy has prospective application as a cathode electrocatalyst in fuel-cell-related technologies with the advantages of superior overall ORR performances, unique structural stability, and easy preparation.